2019
DOI: 10.1136/bmjopen-2019-029727
|View full text |Cite
|
Sign up to set email alerts
|

The use of triclosan-coated sutures to prevent surgical site infections: a systematic review and meta-analysis of the literature

Abstract: Introduction and objectivesSurgical site infections (SSIs) represent a common and serious complication of all surgical interventions. Microorganisms are able to colonise sutures that are implanted in the skin, which is a causative factor of SSIs. Triclosan-coated sutures are antibacterial sutures aimed at reducing SSIs. Our objective is to update the existing literature by systematically reviewing available evidence to assess the effectiveness of triclosan-coated sutures in the prevention of SSIs.MethodsA syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
75
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 62 publications
4
75
2
3
Order By: Relevance
“…Research regarding triclosan-coated sutures is of interest. Although our own work looking at infection rates with this type of suture showed no benefit compared with standard sutures, a large meta-analysis shows a definite benefit of triclosan sutures, 91 and although more expensive, there is an overall cost saving in relation to a reduced infection rate. 119 We have not yet incorporated triclosan-coated sutures into our practice but plan to do so, based on this evidence.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Research regarding triclosan-coated sutures is of interest. Although our own work looking at infection rates with this type of suture showed no benefit compared with standard sutures, a large meta-analysis shows a definite benefit of triclosan sutures, 91 and although more expensive, there is an overall cost saving in relation to a reduced infection rate. 119 We have not yet incorporated triclosan-coated sutures into our practice but plan to do so, based on this evidence.…”
Section: Discussionmentioning
confidence: 71%
“… 90 More recently, we performed a meta-analysis incorporating 25 RCTs and 11,957 patients showed that triclosan-coated sutures significantly reduced the rate of SSI at 30 days (RR 0.73, 95% CI 0.65–0.82). 91 Ten RCTs within this meta-analysis were focused on clean surgery, for which a significantly lower incidence of SSI (149/3029) occurred with triclosan-coated sutures compared to standard sutures (230/1117) (RR 0.71, 95% CI 0.58–0.88). We estimate that the prevention of one SSI saves around £2000 in joint replacement costs – and as such is highly cost-effective.…”
Section: Suture Materialsmentioning
confidence: 99%
“…Sensitivity analysis also documented a significant SSI reduction benefit for clean, clean-contaminated, and contaminated surgical procedures. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Available varieties of triclosan‐coated suture material include Vicryl Plus, Monocryl Plus and PDS Plus Antibacterial sutures . A recent systematic review and meta‐analysis concluded that triclosan‐coated sutures were effective in reducing surgical site infections . The World Health Organization and Centers for Disease Control and Prevention guidelines for the prevention of surgical site infection recommend the use of triclosan‐coated sutures, based on low‐to‐moderate quality evidence…”
Section: Discussionmentioning
confidence: 99%
“…3 A recent systematic review and meta-analysis concluded that triclosan-coated sutures were effective in reducing surgical site infections. 4 The World Health Organization and Centers for Disease Control and Prevention guidelines for the prevention of surgical site infection recommend the use of triclosan-coated sutures, based on low-to-moderate quality evidence. 5,6 Triclosan has a low sensitizing potential and ACD is uncommon.…”
mentioning
confidence: 99%